Pulp revascularization with and without platelet-rich plasma in two anterior teeth with horizontal radicular fractures: a case report - Edison Arango-Gómez; Javier Laureano Nino-Barrera; Gustavo Nino; Freddy Jordan; Henry Sossa-Rojas (Restorative Dentistry & Endodontics, 2019)
Pulp revascularization is an alternative treatment in immature traumatized teeth with necrotic pulp. However, this procedure has not been reported in horizontal root fractures. This is a case report of a 9-year-old patient with multiple horizontal root fractures in 2 upper central incisors that were successfully treated with pulp revascularization. The patient presented for treatment 2 years after the initial trauma, and revascularization was attempted after the initial treatment with calcium hydroxide had failed. Prior to pulp revascularization, cone-beam computed tomography and autoradiograms demonstrated multiple horizontal fractures in the middle and apical thirds of the roots of the 2 affected teeth. Revascularization was performed in both teeth; platelet-rich plasma (PRP) was used in one tooth (#11) and the conventional method (blood clot) was used in the other tooth (#21). Clinical and radiographic follow-up over 4 years demonstrated pulp calcification in the PRP-treated tooth. Neither of the 2 teeth were lost, and the root canal calcification of tooth #11 was greater than that of tooth #21. This case suggests that PRP-based pulp revascularization may be an alternative for horizontal root fractures.